Immunochromatographic Tests for Rapid Diagnosis of Noroviruses - Hiroshi Ushijima (2018)
© 2017 Elsevier Inc. All rights reserved. Immunochromatographic (IC) tests for rapid diagnosis of norovirus infection are now available in many countries. The tests are simple and useful for rapid detection, and they are commonly used in primary care units and outpatient clinics. This chapter first describes the tools for the detection of noroviruses from stool samples, including electron microscopy, latex agglutination, enzyme-linked immunosorbent assay, polymerase chain reaction, and IC test. Then, the chapter focuses on the development, principle, and current and future status of IC tests. The current IC tests are limited by sensitivity, and they may produce false-negative results when a new variant emerges. These are the major areas for future development.